Cardioprotection with Adenosine during Coronary Revascularization (Cardiovascular Journal, 2021)
Background: Postoperative cardiac dysfunction is a common cause of mortality and morbidity associated with CABG Surgery. Adenosine enhances tolerance of the myocardium to ischemic arrest. Therefore, the study on adenosine pre-treatment as an adjunct to cardioplegia in patients undergoing CABG will definitely help to provide better myocardial protection for better postoperative outcome.Methods: Quasi experimental study was done in the Department of Cardiac Surgery, NICVD during July 2012 to June 2014 with patients who underwent conventional CABG surgery. Patients were divided in two groups. Group A: Patients received at regular institutional high-potassium ([K+] = 20 mol/ l) cold (12 °C) blood cardioplegia. and Group B: Patients received 250 μg /kg bolus dose of adenosine pre-treatment, which was immediately followed by high-potassium cold (12 °C) blood cardioplegia after clamp-on. Patients were followed up to evaluate the degree of myocardial damage by measuring perioperative Troponin I, amount of inotropic support, time of assisted ventilation, arrhythmia and mortality.Results: Most of the patients in each group belongs to 51-60 years of age range. There was no difference regarding operative parameters in two groups. Time to arrest was significantly shorter in group B compared to group A, indicating that adenosine has the potential to enhance the efficacy of cardioplegic arrest. Plasma level markers of myocardial damage: cardiac Troponin I (cTnI) obtained from serial venous blood samples post-operatively were significantly lower in group B than group A (p